Interstate Media Wars: The Experience of the Ethiopian Federation - Amanuel Gebru Woldearegay (Modern Africa)
The present study interrogates the interstate media wars that erupted following the emergence of relational troubles among the parties of Ethiopia’s coalition: the Ethiopian People’s Revolutionary Democratic Front (EPRDF). Data from archives and interviews were used to understand the causes and characteristics of the media wars that were mostly fought out on television and other mass media. Findings show that the states used offensive and defensive strategies that included delegitimation, narrativisation and moralisation. Findings further indicate that the most open media war involved the Somali and Oromia states, which used Facebook as their major platform to express an open political hostility relating to their ethnoterritorial disputes in the earliest phases of the conflict. The present study highlights the potential dangers of inflammatory state media deployment in the context of fractured and fragile federations.